Perinatal deaths in Bursa Province, Turkey: an analysis by applying the International Classification of Diseases-perinatal mortality (ICD-PM) system - Metin, Salih (The European Research Journal, 2022)
Objectives: The International Classification of Diseases for Perinatal Mortality (ICD-PM) system is a globally used classification based on the International Statistical Classification of Diseases and Related Health Problems (ICD-10) codes. Moreover, it focuses on the time of death and maternal conditions. Here, we analyzed perinatal deaths by using the ICD-PM system. Methods: This is a retrospective study, performed between January 1, 2020, and March 30, 2022, in Bursa. Perinatal characteristics and the causes of perinatal deaths were recorded. The perinatal deaths were classified according to the ICD-PM system and descriptives were given. Results: The majority of perinatal death cases (119 cases) occurred in the antepartum period. The leading cause of antepartum deaths was unspecified causes (62.2%) followed by fetal growth disorders (9.3%). A total of 63 (53.7%) mothers were healthy (M5) while 27 (22.7%) mothers had medical or surgical conditions (M4). Acute intrapartum events (33.4%) were the commonest cause of intrapartum deaths followed by unspecified causes (26.6%). When neonatal deaths were analyzed, low birth weight/prematurity constitute 59.6% of neonatal deaths. The largest proportion of mothers was healthy in the intrapartum (40%) while maternal complications of pregnancy (M2) was the most commonest classification for neonatal deaths. Conclusions: ICD-PM is a globally used system for classifying perinatal deaths. The time of perinatal death used in this system provides focus on interventions in perinatal care and it encourages comparison between perinatal care centers. We suggest that we might use resources truly to prevent perinatal deaths in our country by using this system.